Coexisting Cooperative Cognitive Micro‐/Nanorobots. Issue 14 (17th May 2019) - Chang, Xiaocong; Tang, Wentian; Feng, Yiwen; Yu, Hao; Wu, Zhiguang; Xu, Tailin; Dong, Huijuan; Li, Tianlong
Abstract: Interaction behaviors are a crucial, distinctive feature of organisms in ecological systems. Inspired by nature, micro‐/nanorobots also show interaction behaviors with a significant number of novel and advanced functionalities. The micro‐/nanoscale size and self‐driven abilities of micro‐/nanorobots have attracted considerable attention for potential applications. The mission of micro‐/nanorobots has evolved from basic mechanical transfer or assistance to a diverse range of complex tasks, such as targeted drug delivery, biosensing, and environmental remediation. Herein, we focus on the interaction behavior of coexisting cooperative cognitive (Tri‐Co) micro‐/nanorobots, summarize recent research, and classify the interactions into three broad types: with the environment, with robot peers, and with human external control. Abstract : Micro machines ! Inspired by nature, micro‐/nanorobots are expected to show interaction behavior with a significant number of advanced functionalities. Recent advances in the interaction abilities of coexisting cooperative cognitive (Tri‐Co) micro‐/nanorobots are discussed. These interactions can be divided into three categories: with the environment, with robot peers, and with humans (see figure).